Islamic Principles to Combat Radicalization in Academia: An Exploratory Study in Pakistani Context - Shah, Samina Batool; Saeed, Riaz Ahmad (Journal of Islamic Thought and Civilization, 2022)
Pakistan’s geopolitical location and events like the Afghan Jihād, 9/11, and the War on Terror have adversely affected our social, religious, and geopolitical realms. Numerous perpetrators are engaged in violent extremism due to their exclusive interpretations of Islamic injunctions, which mainly deviate from the basic Islamic principles. These developments in our region have given rise to the phenomenon of radicalization in the socio-religious and political spheres. Unfortunately, this radicalization has infused the higher education sector and threatened Pakistan’s security and safety. According to this study, ‘radicalization’ is a process in which people or groups adopt extreme social, religious, and political views to discredit or reject others’ coexisting and contemporary ideologies. The status quo, the delicate law & order situation, and developing trends and ideas at the societal level further lead to polarization and division. This paper aims to identify numerous adherents’of radicalization in Higher Education Institutions (HEIs). It also explains the central concept of theological radicalization and how genuine Islamic principles combat these misconceptions. Analytical and exploratory research methodology has been adopted for this study. This research concludes that by adopting the Islamic principles of Waṣatīyyah (Moderation and the Middle Path) and ‘Ilm-al-Eḥsān (to do beautiful things or Excellence) one could lead a successful life as ordained by Allah. A reversal of the rise of radicalism and extremism is possible with the help of moderates and reformers in society and academia to incorporate Islamic socio-religious norms and values. This paper recommends that academia and society must adopt moderation, diversity, and pluralism grounded in Islamic teaching to curb radicalism. Keywords: Combating radicalization, Islamic principles, Pakistani academia, Religious modesty